2019
DOI: 10.31539/bioedusains.v2i2.977
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Media Booklet Berbasis Keanekaragaman Jenis Jamur Makroskopis

Abstract: This study aims to develop a booklet media based on the diversity of macroscopic mushroom species in Lubuklinggau City. The method used is the Research and Development (R&D) method, with two stages of research namely making media booklets and validating media booklets. Data collection using the JAS method. The validity of the booklet with questionnaires for media experts and material experts. Response readability and practicality using a questionnaire questionnaire lecturers and students, knowing the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
3
0
4
Order By: Relevance
“…Menurut Atiko (2019) booklet memiliki ukuran lebih kecil dari buku pada umumnya serta memuat informasi pada topik tertentu serta dilengkapi dengan gambar-gambar yang mendukung. Beberapa penelitian menunjukkan pembelajaran melalui penggunaan booklet dapat meningkatkan pengetahuan (Fitriani & Krisnawati, 2019;Yuliana, dkk., 2019), meningkatkan hasil belajar (Mahendrani & Sudarmin, 2015;Yuliana, dkk., 2019), menumbuhkan keaktifan peserta didik (Mahendrani & Sudarmin, 2015;Pralisaputri, dkk., 2016), serta meningkatkan efektivitas komunikasi (Hapsari, 2013;Rehusisma, dkk., 2017).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Menurut Atiko (2019) booklet memiliki ukuran lebih kecil dari buku pada umumnya serta memuat informasi pada topik tertentu serta dilengkapi dengan gambar-gambar yang mendukung. Beberapa penelitian menunjukkan pembelajaran melalui penggunaan booklet dapat meningkatkan pengetahuan (Fitriani & Krisnawati, 2019;Yuliana, dkk., 2019), meningkatkan hasil belajar (Mahendrani & Sudarmin, 2015;Yuliana, dkk., 2019), menumbuhkan keaktifan peserta didik (Mahendrani & Sudarmin, 2015;Pralisaputri, dkk., 2016), serta meningkatkan efektivitas komunikasi (Hapsari, 2013;Rehusisma, dkk., 2017).…”
Section: Pendahuluanunclassified
“…Pada booklet ini kejelasan gambar tumbuhan yang disajikan sesuai dengan gambar asli tumbuhan obat dan gambar yang disajikan tidak buram atau pecah (Gambar 1.). Adapun tujuan kejelasan tampilan gambar itu penting agar informasi pembelajaran tersampaikan secara efektif (Nugroho, dkk., 2012;Paramita, dkk., 2018) serta gambar mudah dikenali dan mudah ditemukan (Fitriani & Krisnawati, 2019). Indikator keenam yaitu tata letak isi informasi tumbuhan obat yang digunakan oleh masyarakat Kota Pontianak.…”
Section: Aspek Formatunclassified
“…Sehubungan dengan maksud dan tujuan tersebut maka peneliti menetapkan judul penelitian "Pengembangan Media Pembelajaran Booklet Berbasis Inkuiri Pada Materi Sel Kelas XI SMA". (Fitriani et al, 2019).…”
Section: Pendahuluanunclassified
“…Also, it contains material concise and precise (Lubis, 2020). In general, the results showed that booklet can improve students' knowledge in the learning process (Rehusisma, et al, 2017;Silalahi, et al, 2018;Ferdiana, et al, 2016) and the presentation of the material in the booklet is categorized as attractive with good readability, efficient, and practical level for used (Fitriani & Krisnawati, 2019). Furthermore, previous studies have shown that booklet has a positive impact on students' learning and recommended to use as learning media which exploring students' achievements (Abbasi, et al, 2017;Setyaningsih, et al, 2019;Sulaiman, et al, 2019), provide the material for considering the effective and attracts students' attention of learning (Kotzer & Elran, 2012;Paramita, et al, 2018), improve students' learning achievements and learning outcomes (Mahendrani & Sudarmin, 2015;Puspita, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…All researchers mentioned that media can also be an alternative for teachers in providing variations in the teaching and learning process, attracting students' attention, and gaining students understanding of the content material (Muhson, 2010;Panjaitan, et al, 2016;Salyani, et al, 2018;Panjaitan, et al, 2019;Wulandari, et al, 2020;Sari & Harahap, 2021 ). Besides that, media also can improve to develop students' curiosity, interest, and motivation for material presented by teachers in learning activities (Arsyad, 2014;Fitriani & Krisnawati, 2019). In another hand, researchers have examined the opportunities to use the booklet as learning media for students, there some aspects that can develop by using booklet in the learning activities: affective, psychomotor, and cognitive which can be seen as well as to complete students' learning achievement (Abbasi, et al, 2017;Sulaiman, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%